Distinct Distress Symptom Trajectories Over 3 Years Are Associated With Baseline Illness Perceptions in Individuals With Coronary Heart Disease. Issue 5 (26th November 2019) - Chilcot, Joseph; Lee, Ester; Tylee, Andre; Brown, June; Weinman, John; Hotopf, Matthew; Palacios, Jorge E
Abstract: Background: Depression and anxiety symptoms (termed distress) are common among coronary heart disease (CHD) patients and associated with poor outcomes. Illness perceptions predict distinct outcome trajectories in other long-term conditions, yet it is not known how they relate to distress trajectories in CHD. Purpose: This study aimed to examine whether baseline illness perceptions are associated with distress symptom trajectories among primary care CHD patients. Methods: This is a secondary analysis of 803 CHD patients from the UPBEAT-UK study, who completed the Hospital Anxiety and Depression Scale every 6 months for 3 years. Baseline assessments included the Brief Illness Perception Questionnaire. Using latent class growth analysis, Palacios et al. (2018) identified five distinct distress symptom trajectories ("stable low, " "chronic high, " "improving, " "worsening, " and "fluctuating") in this cohort. Adjusted multinomial logistic regression analyses were used to test the association between baseline illness perceptions and distress symptom trajectories. Results: Compared with the stable low distress trajectory, stronger illness identity (odds ratio [OR] = 1.31, p < .01), higher perceived consequences (OR = 1.47, p < .01), illness-related emotion (OR = 1.66, p < .01), and illness concerns (OR = 1.36, p < .01) increased the odds of having chronic high distress. Stronger illness coherence (OR = 0.89, p < .05) and personal (OR = 0.77, p < .01) and treatment control (OR = 0.75, p < .01) reduced the odds of chronic high distress. Worsening distress symptoms were associated with weaker perceptions of treatment control, higher perceived consequences, and greater illness-related concerns and emotions. Conclusions: Illness perceptions of CHD are associated with distress symptom trajectories. Therapeutically modifying unhelpful illness perceptions in CHD patients who experience high levels of distress could potentially improve mental health outcomes. Abstract : Coronary heart disease (CHD) patients who had high levels of distress overtime were likely to hold more negative and unhelpful illness perceptions, including weaker control related beliefs, compared to those with stable-low distress symptoms.